2008
DOI: 10.1136/jmg.2008.060020
|View full text |Cite
|
Sign up to set email alerts
|

Heart-hand syndrome of Slovenian type: a new kind of laminopathy

Abstract: This new heart-hand syndrome should therefore be considered as a new kind of laminopathy. As part of laminopathies with heart involvement, patients presenting with this phenotype and their relatives are at risk for developing sudden cardiac death and should beneficiate from appropriate LMNA genetic diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 29 publications
(43 reference statements)
0
42
0
4
Order By: Relevance
“…Individuals with mandibuloacral dysplasia caused by LMNA mutation have partial lipodystrophy but also mandibular and clavicular hypoplasia, acroosteolysis of the distal fingers, delayed closure of the cranial suture, joint contractures, short adult stature and growth retardation [37]. Several of these phenotypic abnormalities overlap those present in progerias, disorders of accelerated ageing [54].…”
Section: Hj Wormanmentioning
confidence: 93%
See 1 more Smart Citation
“…Individuals with mandibuloacral dysplasia caused by LMNA mutation have partial lipodystrophy but also mandibular and clavicular hypoplasia, acroosteolysis of the distal fingers, delayed closure of the cranial suture, joint contractures, short adult stature and growth retardation [37]. Several of these phenotypic abnormalities overlap those present in progerias, disorders of accelerated ageing [54].…”
Section: Hj Wormanmentioning
confidence: 93%
“…Hence, Emery-Dreifuss muscular dystrophy, isolated dilated cardiomyopathy and limb-girdle muscular dystrophy 1B are actually a spectrum of overlapping clinical phenotypes caused by LMNA mutations, with dilated cardiomyopathy as the unifying feature [35]. LMNA mutations have also been associated with cases of congenital muscular dystrophy with heart involvement and 'heart-hand syndrome', in which cardiomyopathy is associated with congenital limb abnormalities [36,37]. LMNA mutations that cause striated muscle diseases generally lead to amino acid substitutions throughout lamins A and C, small Autosomal-dominant missense mutations in LMNA, the large majority of which cause a change in the surface charge of the immunoglobulinlike fold of lamin A and lamin C, cause Dunnigan-type familial partial lipodystrophy, with selective loss of subcutaneous fat from the extremities, fat accumulation in the neck and face and insulin resistance and diabetes mellitus.…”
Section: Hj Wormanmentioning
confidence: 99%
“…In the Slovenian family, a heterozygous cryptic splice‐site mutation LMNA c.1609‐12T>G was found; expression studies showed abnormal mRNA splicing and a truncated Lamin A/C protein with 14 new amino acids at the C‐terminus (p.E536fsX14) consistent with dominant negative or gain of function mechanism for disease 3. For the LMNA p.Arg335Trp missense mutation, a different molecular mechanism is possible.…”
Section: Figurementioning
confidence: 99%
“…TBX5 for HHS I: Holt–Oram syndrome and LMNA for HHS‐Slovenian type (due to a cryptic splice‐site mutation) are the only two genes found to contribute to HHS 1, 2, 3.…”
Section: Figurementioning
confidence: 99%
“…Two other laminopathies have a cardiac phenotype. The autosomal‐dominant dilated cardiomyopathy 1A linked to LMNA (OMIM #115200) is characterized by an isolated cardiac impairment, while the dilated cardiomyopathy is accompanied by a brachydactyly in hands and feet in the autosomal‐dominant Slovenian type “Heart‐hand” syndrome (OMIM #610140; Fatkin et al., 1999; Renou et al., 2008). Several microRNAs have been described as muscle‐specific and to regulate muscle function, such as proliferation, differentiation, or contractility (Agarwal et al., 2008; van Rooij et al., 2008).…”
Section: Mirnas In Hereditary Laminopathiesmentioning
confidence: 99%